PEMANFAATAN CHAT GPT OPEN AI TERHADAP ANALISIS DAN STRATEGI DALAM MENINGKATKAN PERFORMA PENJUALAN PRODUK SECARA DIGITAL - Julianto, Julianto (JURSIMA, 2023)
The rapid development of technology can produce several new innovations that are beneficial to society such as ChatGPT Open AI. ChatGPT is an artificial language model developed by OpenAI, an artificial intelligence technology company. GPT stands for "Generative Pre-trained Transformer", which refers to the model architecture used in the creation of ChatGPT. The method used in this research is a qualitative method. The results showed that the utilization of ChatGPT allows businesses to be able to conduct in-depth analysis of customer data and product reviews, help identify new problems and opportunities that have not been seen before, assist businesses in developing more targeted and personalized marketing strategies, enable businesses to provide fast and responsive responses to customer inquiries, businesses can quickly identify problems that may occur with the product, This allows for faster repairs and improvements, which in turn can increase customer satisfaction. By utilizing the analysis conducted with ChatGPT, businesses can enter a continuous cycle of improvement. Findings and feedback can be continuously processed to improve products and marketing strategies, ultimately supporting long-term sales growth. Although ChatGPT has a lot of potential, the software has limitations. Understanding the context and human interpretation remains critical to making the right decisions. In addition, ethics in data collection and use must also be prioritized. With awareness and understanding, utilizing ChatGPT in digital product sales analysis and strategy can significantly contribute to achieving business goals.